2004
DOI: 10.1081/jdi-120028540
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Patients with Chronic Renal Insufficiency at Hospital de Clínicas of Porto Alegre, Brazil

Abstract: Chronic renal insufficiency (CRI) decreases reproductive capability. The biggest challenge in monitoring pregnant women with renal disease is to keep the intrauterine environment favorable to the fetus. One of the common prognosis in this kind of pregnancy involves premature birth, restricted growth and mental retardation. Also, the risk of developing complications is higher for the mother. This study focuses on evaluating CRI patients' clinical conditions during pregnancy, checking fetal development and birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 16 publications
0
29
1
3
Order By: Relevance
“…Of the 23 studies (n=505,759 pregnancies), 14 (17)(18)(19)(20)(21)(22)27,28,30,32,33,35,37) of the reported adverse maternal or fetal outcomes in pregnant women with CKD. The definition of CKD varied across the studies.…”
Section: Study Selection and General Informationmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 23 studies (n=505,759 pregnancies), 14 (17)(18)(19)(20)(21)(22)27,28,30,32,33,35,37) of the reported adverse maternal or fetal outcomes in pregnant women with CKD. The definition of CKD varied across the studies.…”
Section: Study Selection and General Informationmentioning
confidence: 99%
“…The overall preeclampsia OR was 10.36 (95% CI, 6.28 to 17.09; P,0.01; Figure 2) in women with CKD compared with women without CKD. Ten studies (2,17,(19)(20)(21)27,28,32,33,35) reported 25,273 failures of pregnancy among 505,038 pregnancies. Compared with the controls, patients with CKD with pregnancy had a significantly higher rate of pregnancy failure (OR, 1.80; 95% CI, 1.03 to 3.13; P=0.04; Figure 3).…”
Section: Effect Of the Kidney Disease On Pregnancymentioning
confidence: 99%
See 3 more Smart Citations